2008
DOI: 10.1111/j.1745-6924.2008.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Fiction is the Abstraction and Simulation of Social Experience

Abstract: Fiction literature has largely been ignored by psychology researchers because its only function seems to be entertainment, with no connection to empirical validity. We argue that literary narratives have a more important purpose. They offer models or simulations of the social world via abstraction, simplification, and compression. Narrative fiction also creates a deep and immersive simulative experience of social interactions for readers. This simulation facilitates the communication and understanding of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
738
3
27

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 960 publications
(793 citation statements)
references
References 162 publications
(242 reference statements)
25
738
3
27
Order By: Relevance
“…Possibly, this is due to the fact that entering the world of a narrative typically involves perspective-taking and experiences of sympathy, empathy, and/or identification with the main protagonist (cf. Mar & Oatley, 2008). These experiences are arguably related to the femininity concept (e.g., caring, affectionate).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, this is due to the fact that entering the world of a narrative typically involves perspective-taking and experiences of sympathy, empathy, and/or identification with the main protagonist (cf. Mar & Oatley, 2008). These experiences are arguably related to the femininity concept (e.g., caring, affectionate).…”
Section: Discussionmentioning
confidence: 99%
“…Stories entail the actions and experiences of one or more protagonists and a plot line with certain schematic elements (e.g., setting, event, attempt, reaction, and consequence; Rumelhart, 1975). In recent years, empirical research has demonstrated that fictional as well as nonfictional narratives can have a pervasive impact on attitudes and beliefs about real-world issues (narrative persuasion; e.g., Green & Brock, 2000; Prentice et al, 1997), on knowledge and memory (Fazio & Marsh, 2008; Marsh, Meade, & Roediger, 2003), and on social abilities and personality (Fong, Mullin, & Mar, 2013; Mar & Oatley, 2008). In some of these studies the stories as a whole or their main narrative arc suggested a particular stance toward a topic (e.g., a story about a psychiatric patient who murdered a child led recipients to have more negative beliefs about the group of psychiatric patients; Green & Brock, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Buckner and Carroll (2007) suggest that mental-state reasoning, perspective-taking, episodic memory, and prospection all depend on a process they call 'self-projection', which involves the mental simulation of events and experiences that transcend the immediate environment. Mar and Oatley (2008) suggest a similar process of simulation to describe the intense social and emotional experiences that literary narratives are capable of evoking (see also Nijhof and Willems, 2015). Finally, Liberman and Trope (2014;Trope and Liberman, 2010) assert that mental representations can all be characterized by how 'psychologically distant' they are from 'a common zero-distance point, which is the experienced reality of me here and now" (Liberman and Trope, 2014, 1).…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%